In vitro rumen fermentation and methane production as affected by rambutan peel powder - Pongsatorn Gunun; Nirawan Gunun; Anusorn Cherdthong; Metha Wanapat; Sineenart Polyorach; Srisuda Sirilaophaisan; Chalong Wachirapakorn; Sungchhang Kang (My University, 2017)
The current study was aimed to determine the effect of rambutan peel powder (RPP) supplementation on in vitro gas production, rumen fermentation characteristics and methane production. The experimental design was a completely randomized design and the dietary treatments were different levels of RPP supplementation at 0, 4, 8, 12, 16 and 20 mg/0.5 g DM. Under this investigation, RPP supplementation did not affect gas production kinetics and in vitro digestibility (p > .05). The concentration of NH3-N decreased linearly with the increasing levels of RPP supplementation (p < .05). Propionate was increased (p < .05) when supplemented with RPP at 16 mg, while acetate and butyrate remained the same. On the other hand, supplementation of RPP decreased methane production (p < .05). This study indicated that RPP at 16 mg could be used as a rumen enhancer for manipulating rumen fermentation.
Keywords: Rambutan; Completely randomized design; Ruminant Nutrition and Digestive Physiology